Perkembangan Pemikiran Tasawuf dan Implementasinya di Era Modern - Meutia Farida (Fakultas Ushuluddin dan Filsafat UIN Ar-raniry Banda Aceh, 2011)
The rapid development of science and technology on one hand created a modern civilization promising advance and ease for life. The hegemony of science and technology generating revolution of industry and information provided abundant of products and sharpened consumptive character of human to fulfill the his biological needs. On the other hand, the advance and hegemony ignore the need for safety, love, dignity, freedom, truth and justice. Because the high civilization causes human being ignored and alienated from God, environment, community, even from himself, which in effect generated disasters and disturbing crisis. To get though with, Tasawuf is believed to be solution to neutralize chaos. The implementation of tasawuf in modern era must be practiced in the frame of syari‟ah by confessing the transformation understanding of Tasawuf. It cannot be practiced by prioritizing maqamat and ahwal alone but by modifying the Tasawuf become dynamic and inclusive in order to it could be digested by spiritual intelligence. The spiritual intelligence is a way into Tasawuf, which is the exploration of spiritual life to get closer to Allah.